Radical contingency, radical historicity and the spread of 'homosexualism': A diachronic corpus-based critical discourse analysis of queer representation in The Times between 1957–1967 and 1979–1990. (August 2022) - Wilkinson, Mark
Abstract: This paper suggests that LGBTQI representation in The Times does more than simply construct queer subjects. Rather, by representing a sexualised Other, the language of The Times necessarily indexes the presence of an unmarked heterosexual population. Moreover, while LGBTQI people have historically been criminalised and discriminated against, a comparison between two historical corpora (1957–1967 and 1979–1990) demonstrates that The Times has consistently used language to suggest that the heterosexual population is, in fact, vulnerable to the threat of non-normative desire and sexual practices. By considering which key phrases and collocations are consistent between the two corpora, it is revealed that the verb spread is used to position heterosexual people as vulnerable to both 'homosexual conduct' in the 1960s and the threat of HIV infection in the 1980s. This is significant because of the considerable influence broadsheet newspapers like The Times had on British public discourse during the latter half of the twentieth century. In order to frame the discussion, the analysis is supported by the theories of radical contingency and radical historicity (Laclau and Mouffe, 1985). The former posits that subject positions are necessarily constituted by what they are not while the latter posits that subjectivities available to us in the present are always the result of political processes from the past. The social ontology of discourse theory (Laclau and Mouffe 1985) therefore provides a lens through which to interpret what diachronic newspaper data reveals about how British social attitudes were changing or staying the same during this time.